Investigation on self-healing performance of asphalt mixture containing microcapsules and survival behaviour of microcapsules. Issue 1 (6th December 2023) - Chen, Yun; Ji, Xiaoping; Si, Botong; Zhang, Zhengming; Shao, Dongye; Zhu, Shiyu; He, Shupeng
ABSTRACT: This paper introduced a preparation method of microcapsules and tests its technical properties. And the survival behaviour of microcapsules in mixture was studied. Then, The influence of microcapsule dosage, mixture properties and healing environment on the mixture self-healing performance was investigated. Finally, the pavement performance of mixture containing microcapsules was studied. Results showed that the microcapsules possessed a smooth surface, a particle size of 14.3 μm, a core content of 85.39%, a hardness of 0.27 GPa, a Young's modulus of 2.49 GPa and good thermal stability. The survival rates of microcapsules were 81.93% and 72.38% at mixing temperature of 130°C and 160°C. Microcapsule dosage of 6%, dense suspension structure, smaller nominal particle size and porosity, large asphalt content, healing temperature of 40–50°C, the healing time of 12 h and dry environment were beneficial to the self-healing performance of the mixture containing microcapsules. After adding microcapsules, the water stability of mixture will decrease, but the high-temperature performance, low-temperature performance and water stability meet the needs of road use.